Optimized fatigue performance of martensitic stainless steel AISI 440C using deep rolling integrated into hardening process (Journal of Mining and Metallurgy, Section B: Metallurgy, 2017)
The deep rolling process can be modified by annealing at appropriate temperature and time to optimize the fatigue performance of metallic materials. The hardening process of the martensitic stainless steel AISI 440C composes of quenching and double tempering processes. That is a great idea to integrate the deep rolling process into the hardening treatment because the heat from the tempering process maybe provides the static strain ageing effects. It was found that the deep rolling process could be integrated faultlessly into the hardening process of the martensitic stainless steel AISI 440C, especially in the middle of the double tempering processes. The heat of the tempering process after the deep rolling process could provide the static strain ageing effects. Consequently greater fatigue lifetime was observed. Moreover, the excellent fatigue lifetime was detected, when the optimized annealing has been performed instead of the second tempering process.